ChemInform Abstract: Hydroamination of Terminal Alkynes with Secondary Amines Catalyzed by Copper: Regioselective Access to Amines. Issue 48 (December 2015) - Bahri, Janet; Blieck, Remi; Jamoussi, Bassem; Taillefer, Marc; Monnier, Florian
Abstract: A series of tertiary amines (III) and (V) is readily prepared by a copper‐catalyzed solvent‐free hydroamination of alkynes (I) with secondary amines (II) and (IV) followed by reduction of intermediate (E)‐enamines.